SEVEN USM SCIENTISTS RECOGNISED AS LOCAL ELITE RESEARCHERS, RECEIVED MALAYSIA'S RISING STAR AWARD - MPRC, Pusat Media & Perhubungan Awam (USM, 2015)
LANGKAWI, KEDAH, 3 September 2015 – The excellent achievements of researchers from Universiti Sains Malaysia (USM) has been further recognised when 7 of them became the recipients of 'Malaysia's Rising Star Award' when their articles were published in internationally acclaimed research journals and were cited the most by their peers worldwide.